DROPBOX Y SU APORTE EN EL APRENDIZAJE COLABORATIVO DE LOS ESTUDIANTES DE BACHILLERATO TÉCNICO DE LA UNIDAD EDUCATIVA VENTANAS, PERIODO ACADÉMICO ABRIL- AGOSTO 2024. - GARCÍA CERVANTES KARLA DAYLY (2024)
This project analyzes the contribution of Dropbox in the collaborative learning of technical high school students of the Ventanas Educational Unit, during the academic period April - August 2024, using qualitative and quantitative methods, interviews and surveys were carried out with students and teachers to evaluate whether The use of this technological platform allows the contribution and exchange of information to manage projects. This study examined how this file management system potentially contributes to improving academic training by providing a shared space to store and manage documents, facilitating access to feedback resources, and facilitating more fluid communication between students. The study begins with a theoretical vision of active learning and the use of digital technologies in education, highlighting its benefits and challenges. Then, the methods used to collect and analyze data are described in detail, delving into the importance of student participation and the supportive role of teachers. In addition, the organizational manner of the schoolchildren was known, which generally affects their academic performance; it was also possible to explore the perception that teachers have with the use of this program. Finally, the research offers necessary recommendations to implement this cloud storage service successfully in other educational contexts, demonstrating the need for continuous training of educators and their learners on how to use technology in their school activities.